KANDUNGAN UNSUR HARA MAKRO N, P, K, SERTA KUALITAS AIR DI BENDUNGAN ALALE, LOMAYA, DAN ALOPOHU (Soil and Environment Journal, 2021)
MACRONUTRIENT CONTENTS OF N, P, K, AND WATER QUALITY IN ALALE, LOMAYA, AND ALOPOHU DAMSThe research aims to know nutrient content of Nitrogen (N), Fosfor (P), and Potassium (K) in water of Alale Dam, Lomaya, and Alopohu dams. This research was conducted in three dams namely in Bendungan Alale, Suwawa District, at Bone Bolango District, Bendungan Lomaya Sub District of Bolango Utara at Bone Bolango District, and Alopohu Dam Bongomeme Sub-district, at Gorontalo Regency. Samplings are taken at 00o32.152' N; 123o10.418' E in Alale Dam, at 00o37.704' N; 123o04.979' E in Lomaya Dam and at 00o37.207' N; 122o53.347' E in Alopohu Dam. This research was conducted for two months ie. from January to February 2017. Laboratory and data analysis were utilized quantitative descriptive method. The results showed that macro nutrient contents of 14.56 ppm N, 9.63 ppm P, and 12.52 ppm K occured in water of Alale Dam; 15.63 ppm N, 10.52 ppm P, and 6.33 ppm K happened in Lomaya Dam water; and Alopohu Dam water had 17.25 ppm N, 11.42 ppm P, and 7.69 ppm K. The highest N and P nutrients are found in the Alopohu Dam, and the highest K is in the Alale Dam. N and P contents in all three dams have exceeded the standard quality of water quality for agriculture. Standard water quality standard of nutrient contents are 10 ppm N and 0,2 ppm P.